Effect of occlusal appliance wear on chewing in persons with Down syndrome - Mazille, Marie-Noëlle; Woda, Alain; Nicolas, Emmanuel; Peyron, Marie-Agnès; Hennequin, Martine (Physiology & behavior, 2008)
The effects of Down syndrome (DS) include orofacial dysmorphology with neuro-motor difficulties and inter-maxillary discrepancy. It is unclear whether improving the inter-arch relationship would suffice to overcome feeding difficulties in persons with DS. This randomized, double-blind, placebo-controlled crossover study is a first step in evaluating the impact of wearing an orthetic intra-oral appliance on chewing variables in 8 subjects with DS (4 males and 4 females; mean age: 27.6 ± 6.1 years). The primary chewing variables were measured through video and electromyographic (EMG) recordings. Secondary variables were (i) modifications in oral health status using the oral assessment for Down syndrome (OADS) questionnaire, (ii) number of inter-arch contacting units (ICUs), (iii) subjects' compliance in wearing the appliance and (iv) subjects' preference between placebo and occlusal appliances. The simultaneous use of EMG and video recordings revealed the presence of lower jaw movements not corresponding to EMG activities in the masticatory muscles. Compared with the pre-treatment situation, wearing an occlusal appliance decreased chewing frequency and increased masticatory time. It is not known whether these changes were indicative of an improvement or a worsening of masticatory function. Persons with DS did not fully adapt to changes in food hardness. A large inter-subject variability was noted, but pre-treatment individual values were not predictive of appliance effect. The maintenance of the number of ICUs obtained at the first installation of appliance and the responses to OADS and satisfaction questionnaires suggested that patients felt more comfortable and that jaw and tongue protrusion were reduced with the appliance.